Evaluating Critical Thinking Skills in Medical Students Isfahan University of Medical Sciences Iran - Shohreh Tashi; Fathieh Mortazavi; Shahram Yazdani; Yasaman Mottaghipour (Kerman University of Medical Sciences, 2013)
Background & Objective: Medical students should learn some skills for better clinical reasoning decision making and using evidence based medicine One of the most important attributes of a successful clinician is the ability of critical thinking in patient care situations The purpose of this study was to evaluate critical thinking skills (analysis evaluation inference and deductive and inductive reasoning) in medical students of Isfahan University of Medical Sciences Isfahan Iran Methods: This nonexperimental study was conducted on 92 men in first third and fifth years of medical education in 20082009 Data were collected using California Critical Thinking Skills Test (form B) and analyzed by SPSS software Statistical tests used for data analysis were ANOVA Duncan Posthoc and Pearson tests Results: The mean scores of 5 subskills were low in all three groups Significant differences were found among three groups in regard to evaluation (P = 048) inductive reasoning (P < 0001) and deductive reasoning (P = 001) Conclusion: It seems that students critical thinking skill is not so desirable in Iran and educational planning should be considered for its development